Positive and Negative Supervisor Development Feedback, Team Harmonious Innovation Passion and Team Creativity - Xiao, Yuchun; Liu, Shuwei; Dai, Ting (Frontiers in Psychology, 2021)
In modern organizations, creative work is usually carried out by teams, and the study of team creativity will therefore have meaningful implications for organization innovation research. The improvement of team creativity is a key management challenge for organization leaders. But our knowledge of how teams respond to and benefit from the supervisor's developmental feedback is limited. This paper draws on the interdependence and knowledge density of team creativity to study how the supervisor's developmental feedback influences creativity at the team level. Our statistical analysis of 94 supervisors and 330 employees finds that positive and negative development feedback from the supervisor both have a positive impact on team creativity, the impact from the negative development feedback is even stronger, and we also finds that the team's harmonious innovation passion mediates the relationship between the supervisor's developmental feedback and team creativity. In addition, we conclude that proactive personality activity moderates the relationship between the supervisor’s positive (negative) developmental feedback and the team's harmonious innovation passion. Our research promotes the development of the study of team creativity in the Chinese cultural context and it is also an important application of developmental feedback that can be incorporated into management practices to enhance team creativity.